The effectiveness of using self-made hyperbaric solution of bupivacaine for unilateral spinal anesthesia - Kozlovska, Iryna; Kozlovskiy, Yurii; Timokhina, Inna; Zakharchuk, Natalia (Pain medicine, 2020)
The main idea of this research was to determine the effectiveness of holding the unilateral spinal anesthesia in comparison with total, positive and negative effects of these manipulations. In Ukrainian medical practice, the technique of spinal anesthesia for analgesia of surgical interventions on the abdominal cavity and lower extremities has been introduced for a long time. One of the main methods is unilateral spinal anesthesia. The study compared: the effectiveness of anesthesia, the duration of anesthesia, the volume of infusion therapy during surgery and the reaction of the cardiovascular system to the manipulations.